Unmasking the Posttraumatic Stress Disorder in Post-Traumatic (2022) Novel - Cahya, Ade Agustina; Dina Amelia (Institut Agama Islam Negeri Palopo, 2024)
This study explores the portrayal of Posttraumatic Stress Disorder (PTSD) in Chantal V. Johnson’s Post-Traumatic (2022), focusing on the main character, Vivian, through the DSM-5 framework. The objective is to examine how Vivian’s unresolved childhood trauma manifests in PTSD symptoms and how these align with the DSM-5 criteria. Using a qualitative research method, the analysis reviews key passages from the novel that depict PTSD-related behaviors, including flashbacks, emotional detachment, avoidance, and self-destructive tendencies. These passages are interpreted in relation to the DSM-5, highlighting how Vivian’s traumatic past continues to influence her psychological state, relationships, and coping mechanisms. The findings reveal that Vivian experiences chronic sleep disturbances, paranoia, hypervigilance, and unhealthy behaviors such as smoking and extreme dieting as forms of maladaptive coping. Her unresolved trauma intensifies these symptoms, affecting her ability to maintain stable personal and professional relationships. The study concludes that the portrayal of PTSD in Post-Traumatic (2022) strongly aligns with DSM-5 criteria, showing how trauma affects emotional regulation, self-perception, and social functioning. Vivian’s substance abuse and self-destructive behaviors serve as coping mechanisms, illustrating the lasting effects of trauma on her mental well-being. By analyzing these dynamics, the study emphasizes the importance of structured psychological frameworks like the DSM-5 in understanding the complexities of trauma in literary characters, providing deeper insights into how PTSD shapes identity and behavior, and illustrating the ongoing cycles of PTSD caused by unresolved trauma.